2020
DOI: 10.1101/2020.05.12.089797
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alleviatory effects of Danshen, Salvianolic acid A and Salvianolic acid B on PC12 neuronal cells andDrosophila melanogastermodel of Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is the most common form of neurodegenerative disorder worldwide. Its pathogenesis involves the hallmark aggregation of amyloid-beta (Aβ). Of all the Aβ oligomers formed in the brain, Aβ42 has been found to be the most toxic and aggressive. Despite this, the mechanism behind this disease remains elusive. With the ability to utilize various genetic manipulations, Drosophila melanogaster is ideal in analysing not only cellular characteristics, but also physiological and behavioural traits… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Zheng Zhiwei demonstrated that Sal B exhibited significant effect on protection against aminoglycoside antibiotics and cisplatin-induced ototoxicity by suppressing the production of ROS and mitochondrial apoptotic pathway, indicating that Sal B could be a preventive or therapeutic agent in the treatment of ototoxic insult-induced hearing loss [ 33 ]. Florence Hui Ping Tan also demonstrated that Danshen water extract (DWE) and its components (Sal A and Sal B) may have therapeutic potential for AD patients and possibly other forms of brain diseases [ 34 ]. However, the result and mechanism of action of Sal B on cell and embryo aging has not been clearly expounded.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng Zhiwei demonstrated that Sal B exhibited significant effect on protection against aminoglycoside antibiotics and cisplatin-induced ototoxicity by suppressing the production of ROS and mitochondrial apoptotic pathway, indicating that Sal B could be a preventive or therapeutic agent in the treatment of ototoxic insult-induced hearing loss [ 33 ]. Florence Hui Ping Tan also demonstrated that Danshen water extract (DWE) and its components (Sal A and Sal B) may have therapeutic potential for AD patients and possibly other forms of brain diseases [ 34 ]. However, the result and mechanism of action of Sal B on cell and embryo aging has not been clearly expounded.…”
Section: Introductionmentioning
confidence: 99%